Pengembangan Trainer Rangkaian Listrik Pada Mata Peljaran Dasar Listrik dan Elektronika Untuk Kelas x Program Keahlian Teknik Audeo Video (TAV) Di SMK Negeri 1 Denpasar - Kadek Odi Arimbawa; Agus Adiarta; I Gede Ratnaya (Jurnal Pendidikan Teknik Elektro Undiksha, 2022)
The purpose of this study was to determine the feasibility and to determine the response of students to the electric circuit trainer, to determine the feasibility of learning media and to determine the response of students to Basic Electrical and Electronics subjects in the Audio Video Engineering Expertise Program (TAV). This research includes the R&D (Research and Development) research model. The study used a questionnaire or questionnaire as an instrument for collecting data from Material Experts, Media Experts and students. The results of the Media Expert test obtained a percentage value of 94.64% with very decent qualifications, the results of the Material Expert test obtained a percentage of 92.5% with very decent qualifications, the results of the small group test resulted in the lowest respondent score, namely respondent R7 with a score of 67. including the very good classification, the results of the large group test the results of the lowest respondent's score, namely the respondent R7 with the same score of 66, including the very good classification. Based on the results of the study, the Electric Circuit Trainer Learning media is suitable for use in the learning process on Basic Electrical and Electronics subjects at the Audio Video Engineering Expertise Program (TAV) of SMK Negeri 1 Denpasar.